2021
DOI: 10.1080/01919512.2021.1889355
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Micropollutant Removal by Ozonation; Interference of Effluent Organic Matter Fractions

Abstract: Ozonation for micropollutant removal from wastewater treatment plant effluent is energy and costintensive because of competition between background organic matter and micropollutants. This study aims to elucidate the interference of different organic matter fractions during the ozonation of micropollutants. Wastewater treatment plant effluent was fractionated using membranes and XAD-8 resin. All membrane and resin fractions were spiked with 18 micropollutants (2 µg/L) and ozonated with 0.25, 0.5 and 1 g O 3 /g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 36 publications
0
11
1
Order By: Relevance
“…The size fractions did not show a significant difference in their interference with MP ozonation (Figure 4.4). This result is different from our previous study where the smallest size fraction (F4) showed a lower interference than the other fractions [177]. The reason for this difference could be a change in the used membranes, resulting in different pressure and cross-flow velocity conditions (section 0).…”
Section: Organic Matter Characteristicscontrasting
confidence: 96%
See 3 more Smart Citations
“…The size fractions did not show a significant difference in their interference with MP ozonation (Figure 4.4). This result is different from our previous study where the smallest size fraction (F4) showed a lower interference than the other fractions [177]. The reason for this difference could be a change in the used membranes, resulting in different pressure and cross-flow velocity conditions (section 0).…”
Section: Organic Matter Characteristicscontrasting
confidence: 96%
“…Membrane fractionation was performed based on van Gijn et al [177] with an updated method (section 0). A Mexplorer test unit (NX Filtration BV, the Netherlands), and three hollow fiber membranes (Pentair, USA) with molecular weight cut-off of 150 kDa, 10 kDa, and 1 kDa were used to separate EfOM into four size ranges: 0.45 µm -150 kDa (F1), 100-10 kDa (F2), between 10 and 1 kDa (F3) and smaller than 1 kDa (F4).…”
Section: Fractionationmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, while considering the role of tertiary treatment in the removal of ARGs, their dose of application (O 3 , UV and chlorine), contact time with the wastewater and wastewater characteristics play a significant role [ 4 , 65 , 156 ]. Additionally, investigations have reported that there are times when O 3 is relatively less effective than the other two disinfection methods, as O 3 gets generally consumed by the organic matter in the effluent [ 157 ]. When coupled with UV treatment, chlorination is reported to be modestly effective for the removal of ARG, integrons that are associated with horizontal gene transfer, and 16s rRNA genes that serve as a marker for bacterial cells [ 158 ].…”
Section: Review Findingsmentioning
confidence: 99%